LUCID: A Quantitative Assay of ESCRT‐Mediated Cargo Sorting into Multivesicular Bodies. (16th November 2015) - Nickerson, Daniel P.; Merz, Alexey J.
Synopsis: Selective targeting of transmembrane cargo proteins to luminal vesicles at endosomes is a process essential for correct regulation of cell signaling pathways and maintenance of cellular health. We present a convenient, microscale, quantitative assay system that monitors exposure of chimeric luciferase‐transmembrane cargoes to cytosol. Luciferase‐chimera signal increases when sorting to the endosome lumen is disrupted, and silencing of signal depends upon luminal delivery of the reporter rather than proteolytic degradation. Abstract : Endosomes are transportation nodes, mediating selective transport of soluble and transmembrane cargos to and from the Golgi apparatus, plasma membrane and lysosomes. As endosomes mature to become multivesicular bodies (MVBs), Endosomal Sorting Complexes Required for Transport (ESCRTs) selectively incorporate transmembrane cargos into vesicles that bud into the endosome lumen. Luminal vesicles and their cargoes are targeted for destruction when MVBs fuse with lysosomes. Common assays of endosomal luminal targeting, including fluorescence microscopy and monitoring of proteolytic cargo maturation, possess significant limitations. We present a quantitative assay system called LUCID (LUCiferase reporter of Intraluminal Deposition) that monitors exposure of chimeric luciferase‐cargo reporters to cytosol. Luciferase‐chimera signal increases when sorting to the endosome lumen is disrupted, and silencing of signal from the chimera depends upon luminal delivery of the reporter rather than proteolytic degradation. The system presents several advantages, including rapidity, microscale operation and a high degree of reproducibility that enables detection of subtle phenotypic differences. Luciferase reporters provide linear signal over an extremely broad dynamic range, allowing analysis of reporter traffic even at anemic levels of expression. Furthermore, LUCID reports transport kinetics when applied to inducible trafficking reporters.